Alternatively Activated Macrophages Drive Browning of White Adipose Tissue in Burns. Issue 3 (March 2019) - Abdullahi, Abdikarim; Auger, Christopher; Stanojcic, Mile; Patsouris, David; Parousis, Alexandra; Epelman, Slava; Jeschke, Marc G.
Abstract : Objective: The aim of this study was to uncover the mediators and mechanistic events that facilitate the browning of white adipose tissue (WAT) in response to burns. Background: In hypermetabolic patients (eg, burns, cancer), the browning of WAT has presented substantial clinical challenges related to cachexia, atherosclerosis, and poor clinical outcomes. Browning of the adipose tissue has recently been found to induce and sustain hypermetabolism. Although browning appears central in trauma-, burn-, or cancer-induced hypermetabolic catabolism, the mediators are essentially unknown. Methods: WAT and blood samples were collected from patients admitted to the Ross Tilley Burn Centre at Sunnybrook Hospital. Wild type, CCR2 KO, and interleukin (IL)-6 KO male mice were purchased from Jax laboratories and subjected to a 30% total body surface area burn injury. WAT and serum collected were analyzed for browning markers, macrophages, and metabolic state via histology, gene expression, and mitochondrial respiration. Results: In the present study, we show that burn-induced browning is associated with an increased macrophage infiltration, with a greater type 2 macrophage profile in the fat of burn patients. Similar to our clinical findings in burn patients, both an increase in macrophage recruitment and a type 2 macrophage profile were also observed in post burn mice. Genetic loss of the chemokine CCR2 responsible for macrophage migration to the adipose impairs burn-induced browning. Mechanistically, we show that macrophages recruited to burn-stressed subcutaneous WAT (sWAT) undergo alternative activation to induce tyrosine hydroxylase expression and catecholamine production mediated by IL-6, factors required for browning of sWAT. Conclusion: Together, our findings uncover macrophages as the key instigators and missing link in trauma-induced browning. Abstract : Supplemental Digital Content is available in the text